Monitoring base excision repair proteins on damaged DNA using human cell extracts. - Parsons, J; Dianov, G (2004)
BER (base excision repair) is a major pathway for the removal of simple lesions in DNA including base damage and base loss (abasic site). We have developed an assay, using formaldehyde cross-linking during repair in human cell extracts, to observe BER proteins involved in the repair of damaged DNA. This approach allows visualization of repair proteins on damaged DNA during BER in human cell extracts and provides a detailed view of the molecular events leading to repair.